1983
DOI: 10.1128/aem.46.3.661-665.1983
|View full text |Cite
|
Sign up to set email alerts
|

Absence of microbial mineralization of lignin in anaerobic enrichment cultures

Abstract: The existence of anaerobic biodegradation of lignin was examined in mixed microflora. Egyptian soil samples, in which rapid mineralization of organic matter takes place in the presence of an important anaerobic microflora, were used to obtain the anaerobic enrichment cultures for this study. Specifically, 14CO2 or [14C]lignin wood was used to investigate the release of labeled gaseous or soluble degradation products of lignin in microbial cultures. No conversion of 14C-labeled lignin to 14CO2 or 14CH4 was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The ¢ndings of this study suggest that the ability to cleave benzyl ether bonds by the rumen microbes could include high molecular mass lignin polymers as long as they are phenolic, but might be restricted to dimers when they are non-phenolic. The amount of cleaved benzyl ether lignin bonds in the rumen that we observed is high, as previous reports [20,21] indicated that anaerobic biodegradation of high molecular mass lignins required a much longer time (over 100 days).…”
Section: Discussionsupporting
confidence: 83%
“…The ¢ndings of this study suggest that the ability to cleave benzyl ether bonds by the rumen microbes could include high molecular mass lignin polymers as long as they are phenolic, but might be restricted to dimers when they are non-phenolic. The amount of cleaved benzyl ether lignin bonds in the rumen that we observed is high, as previous reports [20,21] indicated that anaerobic biodegradation of high molecular mass lignins required a much longer time (over 100 days).…”
Section: Discussionsupporting
confidence: 83%
“…Could the decomposition of such aromatic compounds account for the apparent CO 2 :CH 4 imbalance? The earliest studies suggested that lignin was resistant to decomposition in the absence of O 2 (Hackett et al 1977;Zeikus et al 1982;Odier and Monties 1983), but later work reported that limited anaerobic degradation of lignin is possible under some conditions-particularly in the presence of sulfate or nitrate as electron acceptors (Kaiser and Hanselmann, 1982;Benner et al 1984;Colberg and Young 1985). However, very little was known about the mechanism of anaerobic decomposition of lignin-like compounds until recent studies demonstrated that the major lignin-derived aromatic compounds-syringate and vanillate-also produce equimolar CO 2 :CH 4 under TEA-limited, methanogenic conditions (Kato et al 2015).…”
Section: (Equation 3)mentioning
confidence: 99%
“…1. The 14C label is likely to have been incorporated chiefly into such exposed, less-condensed units during the short maturation of 72 h after the administration of the labeled precursors (14,48), resulting in the formation of more easily degradable lignocelluloses (1,32).…”
Section: Mineralization Of [14cjlignocelluloses Release Of 14co2mentioning
confidence: 99%